Innovation of Fiqh Learning Methods Through Digital Educational Games - Zaenal Mukarom; Imam Tabroni; Mohamad Yudiyanto; Acep Komarudin; Abdul Aziz (International Journal of Education and Digital Learning (IJEDL), 2024)
This study aims to develop and evaluate the effectiveness of Fiqih learning method innovation through digital educational games. In the rapidly evolving digital era, conventional learning approaches are often no longer adequate to attract students' interest and attention. Therefore, this study proposes the use of digital educational games as an alternative method of Fiqh learning, which is expected to increase students' motivation to learn and understand Fiqh materials. This study uses the library research method. Data is collected through observation and documentation, then analyzed qualitatively and quantitatively. The results of the study show that the use of digital educational games in Fiqh learning significantly increases students' interest in learning and understanding. In addition, students showed a positive response to the latest method, which was considered more interesting and interactive compared to conventional learning methods. These findings show that digital educational games have great potential as an innovation in Fiqh learning, and can be widely applied to improve the quality of education in the digital era.